Exploring the impact of managerial leadership practices on the performance levels of employees at Forewin Ghana Limited - Awuah, Lawrencia Boahemaa, (KNUST, 2025)
A thesis submitted to the Department of Human Resources and Organizational Development, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the degree of Master of Business Administration (HRM Option) School of Business, KNUST, School of Business, College of Human and Social Science